Gut-brain axis: Mechanisms and potential therapeutic strategies for ischemic stroke through immune functions - Zhou, Sheng-Yu; Guo, Zhen-Ni; Yang, Yi; Qu, Yang; Jin, Hang (Frontiers in Neuroscience, 2023)
After an ischemic stroke (IS) occurs, immune cells begin traveling to the brain and immune system from the gut and gastrointestinal tract, where most of them typically reside. Because the majority of the body’s macrophages and more than 70% of the total immune cell pool are typically found within the gut and gastrointestinal tract, inflammation and immune responses in the brain and immune organs require the mobilization of a large number of immune cells. The bidirectional communication pathway between the brain and gut is often referred to as the gut-brain axis. IS usually leads to intestinal motility disorders, dysbiosis of intestinal microbiota, and a leaky gut, which are often associated with poor prognosis in patients with IS. In recent years, several studies have suggested that intestinal inflammation and immune responses play key roles in the development of IS, and thus may become potential therapeutic targets that can drive new therapeutic strategies. However, research on gut inflammation and immune responses after stroke remains in its infancy. A better understanding of gut inflammation and immune responses after stroke may be important for developing effective therapies. This review discusses the immune-related mechanisms of the gut-brain axis after IS and compiles potential therapeutic targets to provide new ideas and strategies for the future effective treatment of IS.